1986
DOI: 10.1111/j.1600-0676.1986.tb01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and cholestasis: the in vitro effects of bacterial products on 14C‐taurocholate uptake by isolated rat hepatocytes

Abstract: ABSTRACT‐ Bacterial endotoxins are known to be an important cause of cholestasis, yet not all organisms that cause cholestasis produce endotoxins. In order to determine whether bacterial products other than endotoxins may be involved in the cholestatis process, 14C‐taurocholate (TC) uptake by isolated rat hepatocytes was measured in the presence of mid‐log, stationary and mid‐death phase bacterial broth supernatants from eight common bacterial pathogens. The results were then correlated with a quantitative as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Klebsiella pneumonia has also been reported by others as a cause for sepsis induced cholestasis in neonates and premature infants (15,16). The mechanisms for cholestasis may not be limited to bacterial endotoxins and other bacterial products as have been suggested (17). Minuk et al (17) showed in a rat model that not all Gram‐negative bacteria caused transport inhibition, and there was no correlation between endotoxin concentrations and inhibition of bile acid uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klebsiella pneumonia has also been reported by others as a cause for sepsis induced cholestasis in neonates and premature infants (15,16). The mechanisms for cholestasis may not be limited to bacterial endotoxins and other bacterial products as have been suggested (17). Minuk et al (17) showed in a rat model that not all Gram‐negative bacteria caused transport inhibition, and there was no correlation between endotoxin concentrations and inhibition of bile acid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for cholestasis may not be limited to bacterial endotoxins and other bacterial products as have been suggested (17). Minuk et al (17) showed in a rat model that not all Gram‐negative bacteria caused transport inhibition, and there was no correlation between endotoxin concentrations and inhibition of bile acid uptake. It is evident that endotoxin not only affects bile transport but also plays a role in hepatocyte injury (18).…”
Section: Discussionmentioning
confidence: 99%
“…4 Although cholestatic jaundice is more commonly associated with gram negative bacteraemia, it is also known to occur with gram positive bacteraemia. [14][15][16] Histologically the most prominent finding in bacteraemic patients with jaundice is intrahepatic cholestasis. In addition, Kupffer cell hyperplasia, portal mononuclear cell infiltrates, focal hepatocyte dropout and steatosis have been described.…”
Section: Discussionmentioning
confidence: 99%
“…challenge to the gut microflora; in humans, the liver secretes up to 1 liter of bile per day into the intestines (38). Furthermore, molecules secreted by bacteria, including S. aureus, during infection are an important cause of metabolic cholestasis, an inability of hepatocytes to produce bile (39). Bile is a complex cocktail composed principally of bile salts, phospholipids, cholesterol, proteins, and bilirubin (40).…”
Section: Discussionmentioning
confidence: 99%